Managing criminal justice organizations: an introduction to theory & practice - Kania, Richard R. E. (Lexis Nexis, 2008)
An introduction to criminal justice management -- Management positions in criminal justice -- Historical antecedents -- Leading in criminal justice -- Organizing criminal justice -- Decision-making and planning -- Evaluating, appraising and assessing performance -- Staffing and personnel issues -- Training and education for criminal justice -- Allocating key organizational resources -- Reporting for criminal justice : information management and organizational communications -- Future issues in criminal justice management